Efficacy of moderately hypofractionated simultaneous integrated boost intensity-modulated radiotherapy combined with temozolomide for the postoperative treatment of glioblastoma multiforme: a single-institution experience - Liangzhi Zhong; Lu Chen; Shengqing Lv; Qingrui Li; Guangpeng Chen; Wen Luo; Pu Zhou; Guanghui Li (Radiation Oncology, 2019)
Abstract Purpose Despite recent advances in multimodal treatments, the prognosis of patients with glioblastoma multiforme (GBM) remains poor. The aim of this study was to evaluate the efficacy of moderately hypofractionated simultaneous integrated boost intensity-modulated radiotherapy (SIB-IMRT) combined with temozolomide (TMZ) for the postoperative treatment of GBM. Materials and methods From February 2012 to February 2018, 80 patients with newly diagnosed and histologically confirmed GBM in our institute were reviewed retrospectively. All patients underwent complete resection or partial resection surgery and then received hypofractionated SIB-IMRT with concomitant TMZ followed by adjuvant TMZ. A total dose of 64 Gy over 27 fractions was delivered to the gross tumor volume (GTV), clinical target volume 1 (CTV1) received 60 Gy over 27 fractions, and CTV2 received 54 Gy over 27 fractions. The progression-free survival (PFS) and overall survival (OS) rates and the toxicities were evaluated. Prognostic factors were analyzed using univariate and multivariate Cox models. Results The median follow-up was 16 months (range, 5~72 months). The median PFS was 15 months, and the 1-, 2-, and 3-year PFS rates were 56.0, 27.6, and 19.5%, respectively. The median OS was 21 months, and the 1-, 2-, 3-, and 5-year OS rates were 77.6, 41.6, 32.8, and 13.4%, respectively. The toxicities were mild and acceptable. Age, KPS scores and the total number of TMZ cycles were significant factors influencing patient survival. Conclusion Moderately hypofractionated SIB-IMRT combined with TMZ is a feasible and safe treatment option with mild toxicity and good PFS and OS.